The Simultaneous Optimization of the Nose and Tail Geometry of a High-Speed Train for Drag and Crosswind Stability - Craig, K.J. (Kenneth) (University of Pretoria, 2019)
Dissertation (MEng)--University of Pretoria, 2018.